Análisis comparativo y derecho constitucional - de Vergottini, Giuseppe (2018)
This work presents us with a brief –though by no means plain– overview of the foundations, presuppositions, possibilities and limitations and some concrete examples of what comparative legal survey gives to the field of Constitutional Law.Indicating the capability of comparative legal practice together with a distinct comparative theoretical study of constitutional matters, giving pertinent methodological observations, the Bolognian professor excels at giving the reader acute observations on the nature of the legal comparison, the definition of its scope, the grounds for something to be “comparable”, as well as other interesting topics.An experienced jurist, de Vergottini also underlines the diff erent functions of the various actors in the legal sphere, the role they play by using comparative legal analysis in their work and the practices of foundation and argumentation they employ, as well as the diff erent models and traditions that have arise.